The Tigger movie - Milne, A. A. (Alan Alexander), 1882-1956.; Walt Disney Pictures; Walt Disney Company; Walt Disney Home Video (Firm); Buena Vista Home Video (Firm) ([Burbank, CA] : Walt Disney Home Video ; Distributed by Buena Vista Home Video, 2000)
Tigger's friends help him find his family.
At head of title: Walt Disney Pictures presents.
Based on the Winnie the Pooh works by A.A. Milne.
This film has been modified from its original version to fit a TV screen.
Voices of Peter Cullen, Jim Cummings, John Fiedler, Nikita Hopkins, Andre Stojka, Kath Soucie, Tom Attenborough, John Hurt, and Ken Sansom.
VHS ; Hi-fi Dolby surround stereo ; digitally mastered.
Closed-captioned for the hearing impaired.
Keywords: Tigger (Fictitious character) -- Juvenile films; Winnie-the-Pooh (Fictitious character) -- Juvenile films; Families -- Juvenile films; Friendship -- Juvenile films; Children's films; Animated films; Films for the hearing impaired